PELANGGARAN PRINSIP KESANTUNAN AHOK (AK) DALAM WAWANCARA EKSKLUSIF KISRUH DPRD DKI JAKARTA DI KOMPAS TV - Finda Mia Wulandari* (Universitas Muhammadiyah Jember, 2016)
This study examines the violation of the principle of politeness acted by Ak in the exclusive interview of Jakarta parliament boondcased on Kompas TV. The method used is descriptive qualitative. Data collection used in the study. Is listening and note taking based on the broadcast by Kompas TV. The data analysis applied is Miks and Huberman model, consting data reduction, data presentation and verification. The resuet of the study shows that there was 35,9% of tact maxim violation, 2,5% of generosity maxim violation, 7,7 % of affirmation maxim violation, 45.5% of modesty maxim violation 7,7 % of syimphaty maxim violation.Keywords: violation, politeness maxime.